A Systematic Literature Review of Brain Neurostimulation Therapies for the Treatment of Pain. Issue 7 (8th February 2020) - Deer, Timothy R; Falowski, Steven; Arle, Jeff E; Vesper, Jan; Pilitsis, Julie; Slavin, Konstantin V; Hancu, Maria; Grider, Jay S; Mogilner, Alon Y
Abstract: Objective: To conduct a systematic literature review of brain neurostimulation for pain. Design: Grade the evidence for deep brain neurostimulation (DBS). Methods: An international, interdisciplinary work group conducted a literature search for brain stimulation. Abstracts were reviewed to select studies for grading. Randomized controlled trials (RCTs) meeting inclusion/exclusion criteria were graded by two independent reviewers. General inclusion criteria were prospective trials (RCTs and observational) that were not part of a larger or previously reported group. Excluded studies were retrospective or existed only as abstracts. Studies were graded using the modified Interventional Pain Management Techniques–Quality Appraisal of Reliability and Risk of Bias Assessment, the Cochrane Collaborations Risk of Bias assessment, and the United States Preventative Services Task Force level-of-evidence criteria. Results: Two high-quality RCTs and three observational trials supported DBS, resulting in Level II (moderate) evidence. Conclusion: Moderate evidence supports DBS to treat chronic pain. Additional Level I RCTs are needed to further the strength of the evidence in this important area of medicine, but the current evidence suggests that DBS should be considered as an option in treating complex pain cases.